SIGNIFIKANSI QUDWAH GURU DALAM PEMBELAJARAN SISWA SMP DAN SMA DI ACEH UTARA - Sri Suyanta (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
In the world of education, the exemplary or qudwah teacher is a type of religion. Only in practice is often a problem. Not only is it an integral part of a person's personality, it also involves many contributing factors. In North Aceh, a sample of research on qudwah, it is also recognized that the teacher is a central figure in the educational process that takes place in his school. From the point of view of Indonesian cultural values, the professional teacher is an educator who has the willpower or determination (strength of will, the strength of mind, self-control, and self-discipline) is very high, so obeyed (digger) words and followed (imitated) behavior. North Aceh also indicates that teacher conformity also has dynamics in its diversity.